Variation in soil‐test‐based phosphorus and potassium rate recommendations across the southern USA. Issue 4 (23rd June 2021) - Zhang, Hailin; Antonangelo, Joao; Grove, John; Osmond, Deanna; Slaton, Nathan A.; Alford, Shannon; Florence, Robert; Huluka, Gobena; Hardy, David Herring; Lessl, Jason; Maguire, Rory; Mylavarapu, Rao; et al.
Abstract: Thirteen states associated with the Southern Extension and Research Activities Information Exchange Group‐6 (SERA‐IEG‐6) agreed to share their soil test based P and K rate recommendations for nine major crops. The objectives were to compare fertilizer P and K rate recommendations, to look for opportunities to rationalize similar recommendations across state lines, and to examine challenges to the development of a cooperative regional approach to P and K recommendations. Mehlich‐3 (eight states), Mehlich‐1 (five states), or Lancaster (one state) extractions were the basis of plant available soil P (STP) and K (STK) assessment. Fertilizer recommendation philosophies (sufficiency, build and maintain, and/or hybrid) variation among the states might be the main reason behind such discrepancies. Although a few similarities in P and K rate recommendations were found, the different philosophies, numerical presentations, and extraction procedures drove important recommendation differences. Widespread adoption of the Mehlich‐3 extraction procedure has not reduced variation in fertilizer P and K rate recommendations among the states. Instead, for states using Mehlich 3, soil test critical concentrations ranged from 30 to 75 mg P kg –1 and 60 to 175 mg K kg –1 for corn ( Zea mays L.) grain and warm‐season grass hay production. The adoption of uniform soil testing terminology, sample collection guidelines, extraction methods, and interpretations across common physiographic regions, soils, and state lines remains a challenge. Differences arise because of the different soil orders and properties, climate conditions, and resulting crop responses to added P and K fertilizers. Such differences in soil‐test‐based fertilizer P and K recommendations are state specific and highlight needs to examine the soil testing and recommendation process, make soil test results end‐user friendly, and, when appropriate, standardize fundamental information used in the soil testing guidelines. Core Ideas: Soil test‐based P and K fertilizer recommendations vary widely across the southern U.S. states. Mehlich‐3 and Mehlich‐1 extractions were the basis of plant available soil P and K assessment. Differences in P and K rate recommendations exists even with a consistent set of extractants. Recommendations differences are attributed to philosophical and soil properties differences. More consistent P and K recommendations would enhance the creditability of soil testing.